Effect of the Application of Constraint- Induced Movement Therapy on the Recovery of Affected Hand Function after Stroke - Dalia Mickevičienė; Justina Butkutė; Albertas Skurvydas; Diana Karanauskienė; Mantas Mickevičius (Lithuanian Sports University, 2018)
Background. Research aim was to evaluate the effect of the application of constraint-induced movement therapy on the recovery of affected hand function after stroke. Research hypothesis: The application of constraint-induced movement therapy on the recovery of affected hand function after stroke would be more effective than the application of conventional physiotherapy. Methods. The study employed the Mini Mental State Examination (MMSE), Lovett's test, Modified Movement Assessment Scale (MMAS) hydraulic dynamometer, and Wolf Motor Function Test. Results. Results showed that constraint - induced movement therapy for patients after stroke helps to recover injured hand movement more effectively (p < .05), enhances performance of functional tasks (p < .05) and also increases muscle strength (p < .05) compared to conventional physiotherapy. Conclusions. After the application of the conventional physiotherapy for patients after stroke affected hand movements and functional task performance improved and the hand grip strength increased statistically significantly. Applying the constraint-induced movement therapy for patients after stroke affected hand movements and functional task  performance  improved  and  the  hand  grip  strength  increased  statistically  significantly.  The  application  of constraint-induced movement therapy for patients after stroke statistically significantly more improved the affected hand function than the application of conventional physiotherapy. Keywords:  constraint-induced movement therapy, stroke, hand function, rehabilitation, physiotherapy.